Model Pemasaran Pada Perusahaan Sosial Islam (Islamic Social Enterprise) - Ishak Slamet (ITB AAS INDONESIA Surakarta, 2022)
Islamic Social Enterprise (ISE) is one of the important sectors in the Islamic economy. Many Islamic social companies operate in Indonesia, whether run by individuals, partnerships, or non-profit organizations. Given their current growth, in Indonesia and around the world, studies on specific ISEs founded by individuals have not received serious attention. Moreover, no discussion of the marketing aspects of ISE can be found in the previous literature. Despite all these limitations, the marketing element remains very important for the sustainable development of ISE. The elements of marketing are expected to be very important for ISE, even though the basic goal is a social goal, but there are benefits to be achieved. The purpose of this study is to explore the marketing model in Islamic social enterprises. This is because the purpose of an Islamic social enterprise (ISE) is to serve the Islamic community/needy beneficiaries as well as the customers of the business being run, no matter what level they are at. This study adopts a literature study or literature review approach. The results of this study indicate that not all elements of the marketing mix can be applied to Islamic social enterprises. In addition, this study highlights several spaces to find ways to maintain ISE by implementing the right marketing elements. The results of the study also expand the literature review on ISE.